2022
DOI: 10.1021/acsami.2c04477
|View full text |Cite
|
Sign up to set email alerts
|

Few-Layered MnAl2S4 Dielectrics for High-Performance van der Waals Stacked Transistors

Abstract: The gate dielectric layer is an important component in building a field-effect transistor. Here, we report the synthesis of a layered rhombohedral-structured MnAl2S4 crystal, which can be mechanically exfoliated down to the monolayer limit. The dielectric properties of few-layered MnAl2S4 flakes are systematically investigated, whereby they exhibit a relative dielectric constant of over 6 and an electric breakdown field of around 3.9 MV/cm. The atomically smooth thin MnAl2S4 flakes are then applied as a dielec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…As shown in Figure e, the output curves measured for different gate voltages ( V G ) are linear, which indicates the ohmic contacts when V DS is small. As displayed in Figure f and Table S2, the performance of our FET is comparable to the state-of-the-art MoS 2 transistors with high-κ dielectrics as the gate in terms of SS and on/off ratio, for example, CaF 2 , HfO 2 , ,, Al 2 O 3 , , hBN, MnAl 2 S 4 , and SrTiO 3 . , These results confirm that 2D LaOCl nanoflakes have great potential to serve as an ideal gate dielectric.…”
Section: Resultssupporting
confidence: 70%
“…As shown in Figure e, the output curves measured for different gate voltages ( V G ) are linear, which indicates the ohmic contacts when V DS is small. As displayed in Figure f and Table S2, the performance of our FET is comparable to the state-of-the-art MoS 2 transistors with high-κ dielectrics as the gate in terms of SS and on/off ratio, for example, CaF 2 , HfO 2 , ,, Al 2 O 3 , , hBN, MnAl 2 S 4 , and SrTiO 3 . , These results confirm that 2D LaOCl nanoflakes have great potential to serve as an ideal gate dielectric.…”
Section: Resultssupporting
confidence: 70%
“…[125][126][127] Although significant progress has been made in scalable synthesis of single-crystalline hBN, direct deposition of hBN onto 2D semiconductors remains challenging: current growth condition of single-crystalline hBN is too harsh for most 2D semiconductors as the temperature will cause their thermal decomposition. Besides hBN, a few other 2D materials, including MoO 3 , [128][129][130][131] BiOCl, [132] VOCl, [133,134] and MnAl 2 S 4 , [135] have been investigated as potential layered dielectrics. Their dielectric parameters, along with typical 3D dielectrics, are listed in Figure 10.…”
Section: Layered Dielectricsmentioning
confidence: 99%
“…Other crystalline dielectrics used with 2D TMDs have been reported including mica, , CaF 2 , ,, MoO 3 , , VOCl, MnAl 2 S 4 , molecular Sb 2 O 3 , and SrTiO 3 perovskites. , More work is required to fully evaluate these materials beyond proof-of-concept devices. For example, while the initial demonstration of a top-gated device with mica exhibited low SS = 72 mV/dec and low D IT = 8.8 × 10 11 cm –2 eV –1 , subsequent measurements showed that long-term stability of mica encapsulated devices were poor due to the strong hydrophilism of mica trapping adsorbed moisture at the interface …”
Section: Applicationsmentioning
confidence: 99%